Workers' Politics, the Communist Challenge, and the Schuman Plan: A Comparative History of the French Socialist and German Social Democratic Parties and the First Treaty for European Integration. (29th July 2016) - Shaev, Brian
Abstract: The Schuman Plan to "pool" the coal and steel industries of Western Europe has been widely celebrated as the founding document of today's European Union. An expansive historiography has developed around the plan but labor and workers are largely absent from existing accounts, even though the sectors targeted for integration, coal and steel, are traditionally understood as centers of working-class militancy and union activity in Europe. Existing literature generally considers the role coal and steel industries played as objects of the Schuman Plan negotiations but this article reverses this approach. It examines instead how labor politics in the French Nord and Pas-de-Calais and the German Ruhr, core industrial regions, influenced the positions adopted by two prominent political parties, the French Socialist and German Social Democratic parties, on the integration of European heavy industry. The empirical material combines archival research in party and national archives with findings from regional histories of the Nord/Pas-de-Calais, the Ruhr, and their local socialist party chapters, as well as from historical and sociological research on miners and industrial workers. The article analyses how intense battles between socialists and communists for the allegiance of coal and steel workers shaped the political culture of these regions after the war and culminated during a mass wave of strikes in 1947–1948. The divergent political outcomes of these battles in the Nord/Pas-de-Calais and the Ruhr, this article contends, strongly contributed to the decisions of the French Socialist Party to support and the German Social Democratic Party to oppose the Schuman Plan in 1950. Abstract : TRANSLATED ABSTRACTS FRENCH – GERMAN – SPANISH Brian Shaev. Politique des travailleurs, le défi communiste et le Plan Schuman. Une histoire comparative du Parti socialiste français et du Parti social-démocrate d'Allemagne et le premier traité pour l'intégration européenne. Le Plan Schuman pour créer un "pool" des industries du charbon et de l'acier de l'Europe occidentale fut largement salué comme le document fondateur de l'Union européenne contemporaine. Une vaste historiographie se développa autour du plan, mais la main d'œuvre et les travailleurs sont fortement absents des comptes existants, même si ces secteurs visés par l'intégration - le charbon et l'acier - sont traditionnellement compris comme des centres de la militance de la classe ouvrière et de l'activité syndicale en Europe. La littérature existante considère généralement que les industries du charbon et de l'acier eurent pour rôle d'être des objets des négociations du Plan Schuman, mais cet article renverse cette approche. Au lieu de celle-ci, il examine la manière dont politique ouvrière dans le Nord et le Pas-de-Calais en France et la Ruhr en Allemagne, régions clés de l'activité industrielle, influencèrent les positions adoptées par deux partis politiques prééminents, le Parti socialiste français et le Parti social-démocrate d'Allemagne, sur l'intégration de l'industrie lourde européenne. Le matériel empirique combine la recherche d'archives dans les archives de parti et nationales avec des conclusions tirées de l'histoire régionale du Nord/Pas-de-Calais, de la Ruhr, et leurs chapitres des partis socialistes locaux, ainsi que de la recherche historique et sociologique sur les mineurs et les travailleurs industriels. L'article analyse la manière dont des luttes intenses entre socialistes et communistes pour l'allégeance des travailleurs du charbon et de l'acier façonna la culture politique de ces régions après la guerre et culmina durant une vague massive de grèves en 1947. Les résultats politiques divergents de ces luttes dans le Nord/Pas-de-Calais et la Ruhr, soutient cet article, contribuèrent largement à la décision du Parti socialiste français de soutenir et le Parti social-démocrate d'Allemagne pour s'opposer au Plan Schuman en 1950. Traduction: Christine Plard Abstract : Brian Shaev. Arbeiterpolitik, die kommunistische Herausforderung und der Schuman-Plan. Eine vergleichende Geschichte der Sozialistischen Partei Frankreichs, der Sozialdemokratischen Partei Deutschlands und des ersten Abkommens zur europäischen Integration. Der Schuman-Plan zur "Zusammenführung" der westeuropäischen Kohle- und Stahlindustrien ist häufig als Gründungsdokument der heutigen Europäischen Union gefeiert worden. Zum Schuman-Plan gibt es mittlerweile eine umfangreiche historiografische Literatur. Arbeiter und die Arbeiterbewegung tauchen jedoch in den meisten vorliegenden Schilderungen kaum auf, obwohl die zur Integration auserkorenen Sektoren (Kohle und Stahl) traditionellerweise als europäische Zentren der Arbeiterklassenmilitanz sowie gewerkschaftlicher Aktivität gelten. Werden die Kohle- und Stahlindustrien in der bisherigen Literatur im Allgemeinen als Objekt der mit dem Schuman-Plan einhergehenden Verhandlungen betrachtet, so wird in diesem Aufsatz der entgegengesetzte Ansatz verfolgt. Untersucht wird, wie die Arbeiterpolitik in industriellen Schlüsselgebieten wie dem Department Nord/Pas-de-Calais und dem Ruhrgebiet die Positionen zur integration der europäischen Schwerindustrie beeinflusst hat, die von zwei bedeutenden politischen Parteien vertreten wurden: den französischen Sozialisten und den deutschen Sozialdemokraten. Als empirische Grundlage der Untersuchung dienen zum einen Recherchen in Partei- und staatlichen Archiven, zum anderen Studien zur Regionalgeschichte der Departments Nord und Pas-de-Calais und des Ruhrgebiets, aber auch zu den entsprechenden sozialistischen beziehungsweise sozialdemokratischen Ortsgruppen. Darüber hinaus wird auf historische und soziologische Untersuchungen zu Arbeitern aus Bergbau und Produktion zurückgegriffen. Der Aufsatz analysiert, wie die heftige Konkurrenz der Sozialisten und Kommunisten um die Gefolgschaft der Kohle- und Stahlarbeiter die politische Kultur der entsprechenden Regionen in der Nachkriegszeit prägte, um dann während der Welle von Massenstreiks 1947 ihren Höhepunkt zu erreichen. Das politische Ergebnis dieser Kämpfe war im Department Nord/Pas-de-Calais ein anderes als im Ruhrgebiet. Das wiederum trug, so die im Aufsatz vertretene These, dazu bei, dass die Sozialistische Partei Frankreichs beschloss, den Schuman-Plan zu begrüßen, während die Sozialdemokratische Partei Deutschlands sich ihm widersetzte. Übersetzung: Max Henninger Abstract : Brian Shaev. Las políticas obreras, el desafío comunista y el Plan Schuman: una historia comparada del Partido Socialista Francés y del Partido Socialdemócrata Alemán ante el primer tratado para la Integración Europea. El Plan Schuman para "compaginar" las industrias del carbón y del acero en Europa Occidental ha sido celebrado de forma generalizada como el documento fundacional de la actual Unión Europea. De forma creciente se ha desarrollado toda una producción historiográfica alrededor del Plan. Sin embargo, el trabajo y los trabajadores quedan completamente ausentes de los estudios existentes, incluso a pesar de que los sectores objeto de la integración, el carbón y el acero, se han considerado tradicionalmente como centros de militancia de la clase obrera y del activismo sindical en Europa. La literatura existente generalmente ha considerado el papel jugado por las industrias del carbón y del acero como objetivos de las negociaciones del Plan Schuman pero este artículo da la vuelta a tal interpretación. En su lugar en él se analiza como las políticas laborales en los departamentos franceses Nord y Pas-de-Calais y en la región alemana del Ruhr, unas de las principales regiones industriales, influenciaron en las posiciones adoptadas por dos partidos políticos prominentes, el Partido Socialista Francés y el Partido Socialdemócrata Alemán, en la integración de la industria pesada europea. El material empírico combina la investigación archivos estatales como tanto en los centros de documentación de los propios partidos junto con las historias regionales del Nord/Pais de Calais y el Ruhr, y las secciones locales de los respectivos partidos socialistas, así como la indagación histórica y sociológica de los mineros y los trabajadores industriales. En el artículo se analiza cómo la intensa rivalidad entre socialistas y comunistas por la adhesión de los trabajadores del carbón y del acero determinó la cultura política de estas regiones tras la guerra y culminó en una masiva oleada de huelgas entre 1947. En el texto se señala cómo los resultados políticos divergentes de estas pugnas en Nord/Pais de Calais y en el Ruhr, contribuyeron de forma decisiva en la articulación de las decisiones del Partido Socialista Francés, a favor, y del Partido Socialdemócrata Alemán, en contra, respecto al Plan Schuman de 1950. Traducción: Vicent Sanz Rozalén